Insecticidal and mosquito repellent efficacy of the essential oils from stem bark and wood of Hazomalania voyronii - Benelli, Giovanni; Pavela, Roman; Rakotosaona, Rianasoambolanoro; Nzekoue, Franks Kamgang; Canale, Angelo; Nicoletti, Marcello; Maggi, Filippo (Journal of ethnopharmacology, 2020)
ETHNOPHARMACOLOGICAL RELEVANCE: The use of Hazomalania voyronii, popularly known as hazomalana, to repel mosquitoes and resist against insect attacks is handed down from generation to generation in Madagascar. In the present study, we investigated the ability of the essential oils (EOs) obtained from the stem wood, fresh and dry bark of H. voyronii to keep important mosquito vectors (Aedes aegypti and Culex quinquefasciatus) away, as well as their toxicity on three insect species of agricultural and public health importance (Cx. quinquefasciatus, Musca domestica and Spodoptera littoralis). MATERIALS AND METHODS: Hydrodistillation was used to obtain EOs from stem wood, fresh and dry bark. The chemical compositions were achieved by gas chromatography-mass spectrometry (GC-MS). Toxicity assays using stem wood and bark EOs were performed on larvae of Cx. quinquefasciatus and S. littoralis, and adults of M. domestica by WHO and topical application methods, respectively. Mosquito repellent activity of the most effective EO, i.e. the bark one, was determined on human volunteers by arm-in-cage tests, and results were compared with that of the commercial repellent N,N-ddiethyl-m-toluamide (DEET). RESULTS: The H. voyronii EOs were characterized by oxygenated monoterpenes with perilla aldehyde (30.9-47.9%) and 1,8-cineole (19.7-33.2%) as the main constituents. The fresh and dry bark EOs were the most active on Cx. quinquefasciatus and S. littoralis larvae, respectively, with LC50/LD50 of 65.5 mg L-1, and 50.5 μg larva-1; the EOs from wood and fresh bark displayed the highest toxicity on M. domestica (LD50 values 60.8 and 65.8 μg adult-1, respectively). Repellence assay revealed an almost complete protection (>80%) from both mosquito species for 30 min when pure fresh bark EO was applied on the volunteers' arm, while DEET 10% repelled >80% of the mosquitoes up to 120 min from application. CONCLUSION: The traditional use of the bark EO to repel insects has been demonstrated although an extended-release formulation based on H. voyronii EOs is needed to increase the repellent effect over time. A wide spectrum of insecticidal activity has been provided as well, suggesting a possible use of H. voyronii EOs in the fabrication of green repellents and insecticides useful to control mosquito vectors and agricultural pests.
Keywords: larva; Spodoptera; Mosquito repellent; oleje prchavé; Culex quinquefasciatus; Humans; diethyltoluamid; Larva; Zika virus; zvířata; Aedes; Time Factors; Plant Oils; Wood; Insecticides; moucha domácí; Mosquito Control; Plant Bark; Musca domestica; repelenty proti hmyzu; kůra rostlin; dřevo; moskyti - kontrola; Dengue; Culex; oleje rostlin; časové faktory; Hernandiaceae; Insect Repellents; Houseflies; Spodoptera littoralis; Animals; lidé; Oils, Volatile; Aedes aegypti; DEET